1992
DOI: 10.1111/j.1440-1681.1992.tb00463.x
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandins and Systolic Blood Pressure, but Not Angiotensin Ii, Independently Affect Atrial Natriuretic Peptide Levels in Man

Abstract: 1. Two hours after a single dose of indomethacin (INDO), plasma renin activity (PRA) and atrial natriuretic peptide (ANP) levels decreased, which is consistent with an effect of lowering prostaglandins (PG). 2. After 48 h of INDO, PRA remained low but ANP had increased, which is consistent with the known effect of prostaglandin inhibitors to cause sodium retention, with a resulting volume expansion. 3. Infusions of angiotension II (AII), which raises diastolic blood pressure (BP) 20 mmHg or more, consistently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1993
1993
1999
1999

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Whereas a significant change in the present study was not found, such a fall in responsiveness would explain the negative correlation between aldosterone and age in the absence of a negative correlation between PRA and age. The stimulation of ANP by A11 in the present study can be explained by a direct effect of blood pressure rise (Burnett et al 1989) on ANP (supported by the correlation between ANP slope and pressor slope) and by an effect of A11 on ANP mediated by prostaglandins (Klemm et al 1992). There was no apparent effect of age on basal ANP or on the ANP response to AIL Our own unpublished observations (1992) in 260 subjects aged 1-77 years and those of McKnight et al (1989) suggest that ANP changes little with age until after 70 years of age, when levels rise.…”
Section: Discussionmentioning
confidence: 79%
“…Whereas a significant change in the present study was not found, such a fall in responsiveness would explain the negative correlation between aldosterone and age in the absence of a negative correlation between PRA and age. The stimulation of ANP by A11 in the present study can be explained by a direct effect of blood pressure rise (Burnett et al 1989) on ANP (supported by the correlation between ANP slope and pressor slope) and by an effect of A11 on ANP mediated by prostaglandins (Klemm et al 1992). There was no apparent effect of age on basal ANP or on the ANP response to AIL Our own unpublished observations (1992) in 260 subjects aged 1-77 years and those of McKnight et al (1989) suggest that ANP changes little with age until after 70 years of age, when levels rise.…”
Section: Discussionmentioning
confidence: 79%